Descriptions of little-known and unknown morphs of Periphyllus acerihabitans Zhang (Hemiptera: Aphididae: Chaitophorinae) - Wieczorek, Karina; Qiao, Ge-Xia; Sano, Masakazu; Yoshitomi, Hiroyuki; Kanturski, Mariusz (Zootaxa, 2016)
Periphyllus acerihabitans Zhang, 1982, associated with Acer buergerianum, is known only from the original description from China. Based on the type series and specimens collected in Japan, we re-describe apterous and alate viviparous females of P. acerihabitans and describe dimorph (aestivating nymph) and oviparous female in detail with illustrations. This is the first record of this species from Japan. The differences between P. acerihabitans and a related species P. viridis (Matsumura, 1919) are discussed. Keys to similar species: P. acerihabitans, P. viridis and P. californiensis (Shinji, 1917), associated with A. buergerianum or A. pictum subsp. mono, are provided.